The ground state of an impurity fluctuating between two magnetic p configurations - Baliña, Marcelo; Aligia, Armando Ángel (Comisión Nacional de Energía Atómica; Argentina)
Fil: Baliña, Marcelo Comisión Nacional de Energía Atómica; Argentina